Três ensaios sobre a agroindústria canavieira no Brasil: história das estratégias empresariais do setor, convergência da produtividade e estudos de casos - Cattelan, Renata (2024)
Historically, the sugarcane sector coped with strong subsidies, regulation and government support until 1990, when the government gradually withdrew from these tasks and promoted commercial opening. To remain in the market, agribusinesses need to establish a more competitive production system in the face of competition and instability in international trade. This movement accentuated the heterogeneities that already existed between Brazilian plants/distilleries and, together with other factors, led many agribusinesses to bankruptcy from 2008/2009 onwards. Considering this scenario, the general objective of this thesis is to verify whether there is convergence in sugarcane productivity in Brazil and to analyze how companies in the sector are operating to remain in the market. To achieve the general objective, this thesis was divided into three different specific objectives, which comprised three essays. The objective of the first essay was to carry out a historical analysis investigating the results of the strategies adopted by the sugarcane sector in response to actions or events that affected the activity, as well as highlighting the prospects for recent opportunities and challenges. The second specific objective was to evaluate whether there was convergence in land productivity for sugarcane between 2006 and 2017 for Brazilian microregions, and to verify the contribution of some variations to this convergence. To this end, a methodology adopted for spatial econometrics seeks to control the spatial dependence and heterogeneity of the sample. The third essay aims to analyze and characterize the strategies of two plants in Paraná in the light of strategy theories, in order to situate them in terms of the procedures used for the company's sustainability and expansion in the sector. To this end, questionnaires were applied, with the case study being the stipulated methodological technique. The results of the first test demonstrated that, historically, most actions are exogenous to the sector and that the measures taken in each context also largely come from government measures. It is not possible to visualize joint strategies of sugarcane producers aimed at anticipating challenges or changes in the market, but they promoted the mitigation of problems when they reached the sector. For the second test, it was concluded that there was absolute and conditional convergence of productivity for all Brazilian regions, however, each region has a different convergence process, and the factors that promote this convergence are also different. Regarding the third specific objective, the results that demonstrated that the two plants have room for progress in terms of internal strategic alignment and the insertion of technologies stand out. Management is indicated as an influential factor in the failure of companies by both respondents, which corroborates other research already carried out. It also suggests that advances related to quality management, using appropriate strategies, can lead companies to long-term success. Based on the findings of the three essays, it is possible to conclude, responding to the general objective and confirming the research thesis, that productivity differences in Brazil are reducing, but public or private actions aimed at growth for the sector must consider regional differences. Furthermore, from a microeconomic point of view, it is confirmed that business management is central to the sustainability of sugarcane agro-industries.